Monstrosities and Hauntings of Brazilian Folklore: an Analysis of Folkcommunication and Folkmidia in Piteco - Ingá (Revista Internacional de Folkcomunicação, 2018)
This paper focus in the representations of the hauntings of the brazilian folklore in the comic book Piteco – Ingá, writen by the author Shiko and published in the Graphic MSP, a comic books collection that intends to give a more adult and serious look to classical characters created by Maurício de Souza. Shiko uses in his narrative brazilian folkloric creatures, as Boitatá and Caipora. The way that they are represented, in a more scary way and different from the usual, will be analyzed within the folkcomunicação and folkmídia concepts, to comprehend how this folkloric elements are modified by the author, trying to get new readers and, in the same way that well know comics characters became amazing again, the author also make that monsters that everybody are used to became again scary. Hauntings; Comic Books; Folkcomunicação.